Pengaruh TI dan Kompetensi SDM terhadap Kualitas Laporan Keuangan Pemerintah Daerah: Peran Pengendalian Internal - Ifrah, Marsyanda; Elviani, Sri; Andri, Shofwan (UNIVERSITAS DHARMAWANGSA, 2025)
Thisi researchi investigates thei effecti ofi informationi technology utilization andi humani resource competencei oni thei quality ofi financiali reportsi ini locali governmenti institutions, i withiiinternali controli systemsi actingi asi ai mediatingi variable. i Thei studyi reliesi oni primaryi datai gatheredi fromi financei staffi withini thei Regionali Apparatusi Worki Unitsi (SKPD) i ofi Medani City. i Ai purposivei samplingi methodi wasi applied, i involvingi 100i selectedi respondents. i Thei analysisi wasi carriedi outi usingi pathi analysisi throughi thei SmartPLSi 4i application. i Thei findingsi showi thati thei applicationi ofi informationi technologyi significantlyi influencesi internali controli systems, whereasi humani resourcei competencei doesi not. i Furthermore, i wheni internali controli isi consideredi asi ai mediatingi factor, i informationi technologyi stilli exhibitsi ai notablei impacti oni thei qualityi ofi financiali reporting, i whilei thei rolei ofi humani resourcei competencei remainsi insignificant.